A moderate dose of alcohol selectively reduces empathic accuracy - Thiel, Freya (Psychopharmacology (Berl), 2018)
RATIONALE: Drinking alcohol is associated with various interpersonal effects, including effects on cognitive empathy. Empathic accuracy (EA) is a form of cognitive empathy concerned with perceivers’ accuracy in inferring a target’s thoughts and feelings. The effects of alcohol on EA have not previously been studied. OBJECTIVES: We examined the effect of a moderate alcohol dose on EA in social drinkers. METHODS: Fifty-four men with varying levels of hazardous drinking according to the Alcohol Use Disorders Identification Test (AUDIT) participated in a randomized, double-blind, between-group study. The alcohol group received 0.56 g/kg alcohol in a vodka and tonic-mixed drink. The placebo group received tonic, with 4 ml of vodka sprayed on top. All participants performed an EA task that involved watching 16 videos of people narrating positive and negative emotional autobiographical events and continuously rating how targets felt while narrating. RESULTS: There were no significant main effects of beverage condition on the EA task. There was an effect of the condition by AUDIT interaction for EA on the positive videos. Post-hoc simple contrasts revealed that in participants with lower AUDIT scores, the alcohol condition had lower EA for positive videos than the placebo condition. No significant main effect for condition occurred in the participants with higher AUDIT scores. CONCLUSIONS: The effect of condition in participants with lower AUDIT scores indicates alcohol selectively reduced EA in individuals low on hazardous drinking. This suggests either alcohol-induced impairments of EA for positive events or a positivity bias in men at low risk for alcohol dependency. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00213-018-4859-y) contains supplementary material, which is available to authorized users.